Schwannoma of the plantarmedial aspect of the foot: A case report. (June 2019) - Merritt, Gerald; Ramil, Madelin; Oxios, Adam; Rushing, Calvin
Highlights: This case demonstrates an abnormal location of a schwannoma on a branch of the medial plantar nerve. Only 11 reports of forefoot schwannomas have been reported and none have been reported on a branch of the medial plantar nerve. This case report discusses the importance of the recognition of a schwannoma, through imaging and histology and also on physical exam. It also discusses treatment options and differential diagnosis. Overall this case report will help raise awareness of schwannomas and their locations. Abstract: Schwannomas of the common medial plantar nerve branch are rare solitary nerve sheath tumors. Fewer than a dozen cases have since been described in the literature, most of which were initially misdiagnosed as ganglion cysts. The case of a 56-year-old male who developed a painful mass on the plantar medial hallux, misdiagnosed as a ganglion cyst, is presented. After surgical intervention and pathological analysis the patient was diagnosed as having a schwannoma. A schwannoma is a slowly growing neoplasm of Schwann cell origin. It is very rare for a schwannoma to transform into a malignant lesion and usually occurs in individuals between the ages for 20-50. Schwannomas usually have a predilection for the head and upper extremities and is very rare in the foot and ankle. The principal treatment of a schwannoma is surgical excision, which eliminates symptoms and can correctly diagnose the mass. Even though schwannomas of the foot have been reported in literature, this case demonstrates an abnormal location on a branch of the medial plantar nerve. Level of Clinical Evidence : Level 4 of Evidence.